(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Emphysematous cystitis is a rare form of urinary tract infection but may progress rapidly to severe infection, leading to bacteremia, septic shock, and multiorgan failure, particularly in patients with poorly controlled diabetes mellitus. Case Presentation: A 78-year-old woman with poorly controlled type 2 diabetes mellitus was admitted with septic shock secondary to a urinary tract infection. Computed tomography demonstrated gas within the bladder wall and lumen, with the extension of gas into the perivesical tissue; urine culture was positive for Escherichia coli. Despite non-elevated initial lactate levels, the patient presented with severe fluid-refractory hypotension requiring vasopressors. After resuscitation, intravenous antibiotics, bladder drainage, and glycemic control, the patient recovered well, was discharged after 12 days, and showed no residual lesions on ultrasonography at a 4-week follow-up. Conclusion: Emphysematous cystitis is a rare condition but may progress rapidly and severely. Early diagnosis based on clinical findings combined with imaging, especially CT scans, together with intensive resuscitation, antibiotic therapy, bladder drainage, and control of underlying risk factors plays a decisive role in improving treatment outcomes.